2018
DOI: 10.3892/mmr.2018.9714
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated growth factor exudate enhances the proliferation of human periodontal ligament cells in the presence of TNF‑α

Abstract: The purpose of this study was to evaluate the effects of concentrated growth factor exudate (CGFe) on human periodontal ligament cells (hPDLCs) stimulated by tumor necrosis factor (TNF)-α. From the peripheral blood of healthy donors, CGFe was prepared according to the Sacco protocol after 7 days of incubation. The hPDLCs were cultured by a tissue explant method and identified with anti-vimentin and anti-cytokeratin antibodies. Cells were subjected to four different treatments: i) Control; ii) TNF-α (10 ng/ml);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…Because of the fibrin matrix of platelets, leukocytes, and high concentrations of many growth factors (e.g., TGF-β1, PDGF-BB, VEGF, IL-1β, and IL-6) in CGF preparations [19], CGF can promote the proliferation and osteoblast differentiation of bone marrow cells and then promote wound healing processes and new bone formation [37]. Li et al recently reported that CGF not only has an osteogenic effect on human periodontal ligament cells (hPDLCs) in a normal culture, but also promotes hPDLCs osteogenesis in a TNF-α-induced inflammatory microenvironment [38].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the fibrin matrix of platelets, leukocytes, and high concentrations of many growth factors (e.g., TGF-β1, PDGF-BB, VEGF, IL-1β, and IL-6) in CGF preparations [19], CGF can promote the proliferation and osteoblast differentiation of bone marrow cells and then promote wound healing processes and new bone formation [37]. Li et al recently reported that CGF not only has an osteogenic effect on human periodontal ligament cells (hPDLCs) in a normal culture, but also promotes hPDLCs osteogenesis in a TNF-α-induced inflammatory microenvironment [38].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CGF, there are limited studies available in relation to periodontal regeneration. Its use has been proposed in dentistry for various situations, ranging from the filling of extraction sockets [70] to the filling of a cavity after cystectomy [71], sinus augmentation procedures [63,72,73], simple GBR procedures [74,75] or as a membrane support in recession coverage [28,[76][77][78]. It was demonstrated to possess the capacity to accelerate new bone formation [79].…”
Section: Periodontal Regenerationmentioning
confidence: 99%
“…However, comparative studies between them have been conducted on osteogenic differentiation of stem cells of the apical papilla (Hong, Chen & Jiang, 2018) and animal bone defect repair (Park et al, 2016; Kim et al, 2014), only a few studies support this. Both L-PRF (Li et al, 2018; Duan et al, 2018) and CGF (Yu & Wang, 2014; Qiao & An, 2017; Li et al, 2019) have been reported to be effective in osteogenic differentiation of PDLFs. However, it has not been previously evaluated whether CGF used for PDLFs differentiation has better attributes than L-PRF.…”
Section: Introductionmentioning
confidence: 99%